Was ist uns die Gesundheit wert? Probleme der nächsten Gesundheitsreformen und ihre Lösungsansätze - Klaus-Dirk Henke (Technische Universität Berlin, Fakultät Wirtschaft und Management, 2004)
"Wer bezahlt was und an wen"? - dies ist eine zentrale Frage im deutschen Gesundheitswesen. Sie muss beantwortet werden, wenn durch zukünftige Reformen eine dauerhafte Finanzierung gewährleistet werden soll. Die Mittelaufbringung, sei es über Steuern, Sozialversicherungsbeiträge, Krankenversicherungsprämien, durch Selbstbeteili-gung oder direkt aus den Konsumausgaben, steht auch im internationalen Zusammenhang zur Diskussion. Dabei zeigt sich, dass die Verwendung dieser Mittel für die Bezahlung und Vergütung der ambulant oder stationär erbrachten Gesundheitsleistungen ebenfalls reformbedürftig ist. – – "Who pays what and to whom"? this is one of the central questions in the German health care system. This question must be answered to guarantee a sustainable system of financing. Taxes, social security contributions, health insurance premiums, co-payments, and out-of pocket-expenditures are internationally under review. The process of spending these ressources in order to pay health care services needs not only a solid analysis but a major reform as well. The basis of this article is a new framework including a minimum insurance obligation (basis health care for all) with freedom to choose between different health insurances and benefit structures and through different service packages.The minimum insurance obligation includes more competition within the production of health services, a decoupling of contributions from the wage bill and the build-up of more capital. Innovations in financing, providing and reimbursing health care services are indispensable for a cost-effective health insurance and health care provision that meet the needs of the population.
Keywords: 330; Gesundheitsreform; Gesundheitsfinanzierung; Deutschland; Basisgesundheitsversorgung